2015
DOI: 10.1111/jth.12795
|View full text |Cite
|
Sign up to set email alerts
|

A novel conditional platelet depletion mouse model reveals the importance of platelets in protection against Staphylococcus aureus bacteremia

Abstract: Background Platelets are critical cells for maintaining vascular hemostasis but their activities in other processes are becoming apparent. Specifically, the ability of platelets to recognize and respond to infectious agents is an important area of investigation. To understand the physiological roles of platelets in vivo, most researchers have used antibody-mediated platelet depletion, which has certain limitations. Objective To develop an optimal system to study the contribution of platelets to protection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 58 publications
8
77
1
1
Order By: Relevance
“…Platelets engage the immune system by interacting with various immune cells (34, 35), and participate in both innate and adaptive immune responses. Our recent publication indicate that platelets provide protection to S. aureus infection (19). Based on this observation, the goal of the present study was to further elucidate the mechanistic details of how platelets promote protection against S. aureus infection and whether this occurs directly and/or through the potentiation of leukocytes antimicrobial functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelets engage the immune system by interacting with various immune cells (34, 35), and participate in both innate and adaptive immune responses. Our recent publication indicate that platelets provide protection to S. aureus infection (19). Based on this observation, the goal of the present study was to further elucidate the mechanistic details of how platelets promote protection against S. aureus infection and whether this occurs directly and/or through the potentiation of leukocytes antimicrobial functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports by us and others showed that platelets functionally contribute to protection against S. aureus infection (1923). Using our novel inducible platelet-depleted mouse model, we demonstrated that platelet-depleted mice have high bacterial burden in kidneys, a more severe cytokine storm, and decreased survival compared to WT counterparts (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A therapeutic lacking hemorrhage risks would provide an important potential advance for the field. However, this is a parameter that would need to be assessed clinically, since mice are less dependent on platelet activation for hemostasis than humans [41]. …”
Section: Therapeutic Opportunities For Pld Inhibitionmentioning
confidence: 99%
“…Mice received 100 ng of diphtheria toxin (DT) intraperitoneally 24 hours before TBI (1000 cGy) and were analyzed 48 hours after irradiation. Monocytes, macrophages, or megakaryocytes were depleted in transgenic mice expressing iDTR on lysozyme2-expressing (LYZ-Cre) 24 or PF4-expressing cells, 25,26 respectively. Mice received daily intraperitoneal injections of DT (100 ng) for 6 days, received TBI on day 4 (1000 cGy), and were analyzed 48 hours after irradiation.…”
Section: In Vivo Cell Depletionmentioning
confidence: 99%